In Their Own Hands: Young People and Self-Justice Retaliation in Germany - Schwarzenbach, Anina (Crime & delinquency, 2023)
Strong and viable modern states have limited the use of private force to narrowly-defined situations of self-defense. Yet, evidence from crime surveys shows that a significant proportion of violent and property crimes is not reported to police. Instead of calling the police, people either take no action or employ a variety of mechanisms, including retaliation, to settle disputes. Drawing on data from a survey of 2,921 young people in two German cities, we investigate the propensity of adolescents to resort to self-justice retaliation. The results show widespread propensity to engage in retaliatory actions, particularly among adolescent males of low socio-economic status. Further, attitudes to the police, unsupervised routine activities, and delinquency-related variables were the most influential correlates of propensity to engage in retaliatory actions.